2001
DOI: 10.1136/bjo.85.5.567
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation for partial limbal stem cell deficiency

Abstract: Aim-To examine the eYcacy, safety, and long term outcomes of amniotic membrane transplantation for corneal surface reconstruction in cases of partial limbal stem cell deficiency. Methods-17 eyes of 15 patients with partial limbal stem cell deficiency underwent superficial keratectomy of the conjunctivalised corneal surface followed by amniotic membrane transplantation. Cases were followed up for at least a year. Results-All eyes exhibited a stable, intact corneal epithelial surface after a mean follow up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
1
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 54 publications
5
113
1
7
Order By: Relevance
“…Failure of attainment of corneal epithelial phenotype of healing in case 9 reconfirmed the common belief that AMT alone is insufficient in cases with total limbal dysfunction. 27 The initial and consistent finding in all patients was a reduction in the ocular inflammation in the early phase after AMT as evidenced by a decrease of conjunctival and limbal hyperaemia, and corneal oedema. We observed that AMT could improve visual acuity, probably owing to both corneal surface restoration and improvement of corneal transparency.…”
Section: Discussionsupporting
confidence: 56%
“…Failure of attainment of corneal epithelial phenotype of healing in case 9 reconfirmed the common belief that AMT alone is insufficient in cases with total limbal dysfunction. 27 The initial and consistent finding in all patients was a reduction in the ocular inflammation in the early phase after AMT as evidenced by a decrease of conjunctival and limbal hyperaemia, and corneal oedema. We observed that AMT could improve visual acuity, probably owing to both corneal surface restoration and improvement of corneal transparency.…”
Section: Discussionsupporting
confidence: 56%
“…Many diverse action mechanisms have been ascribed to the amniotic membrane for its supplanting with a new basement membrane and a stroma that can suppress inflammation, scarring and angiogenesis (for review see [95]). Importantly, amniotic membrane transplantation alone is sufficient to restore the normal corneal epithelial phenotype in human corneas with partial limbal SC deficiency [96][97][98], indicating that amniotic membrane helps expand residual limbal epithelial SCs in vivo. The above clinical discovery has led others to successfully transplant such an ex vivo expanded human limbal epithelial tissue to treat human corneas with total limbal SC deficiency [34,99,100].…”
Section: Will Restoration Of Niche Support Be Critical For Ex Vivo Exmentioning
confidence: 99%
“…As propriedades antiinflamatórias, antiangiogênicas e moduladoras da cicatrização da membrana amniótica puderam ser constatadas pelo bom aspecto clínico pós-operatório da maioria dos casos estudados, que apresentaram superfície córneo-conjuntival mais estável, sem erosões e com menos inflamação ou formação de cicatrizes (17,(20)(21) . Alguns autores mostraram resultados satisfatórios com a utilização de membrana amniótica como enxerto após remoção de tumores conjuntivais em 16 olhos (3,16) .…”
Section: Discussionunclassified